Peran Hukum Progresif dalam Menyelesaikan Konflik Pidana Masyarakat: Tantangan dan Solusi Hukum Berkeadilan - Mohd. Yusuf DM; Geofani Milthree Saragih; Dodi Mustika; Fadler Hidayat; R. Dicky Wirawan L.; Rita Anggraini (IAIN Langsa, 2025)
This condition gives rise to various problems, particularly in resolving criminal conflicts involving vulnerable groups and local communities. This study aims to analyze the role of progressive law in resolving community criminal conflicts, as well as to identify the challenges and equitable legal solutions offered through this approach. The research employs a qualitative library-based methodology by analyzing scholarly literature, statutory regulations, and academic works relevant to progressive law and criminal conflict resolution. The findings indicate that progressive law is capable of providing more humane and contextual solutions through the application of restorative justice, penal mediation, and community-based approaches. Nevertheless, its implementation still faces structural, cultural, and institutional obstacles. Therefore, a paradigm shift in law enforcement and strengthened commitment from all stakeholders are required so that progressive law can function optimally in realizing sustainable justice.